Paroxysmal atrial fibrillation: treatment choice - B. A. Tatarsky (Кардиоваскулярная терапия и профилактика, 2007)
Characteristics and classification of various paroxysmal atrial fibrillation (AF) forms are presented. Main indications for sinus rhythm restoration are listed, together with characteristics of principal medications used for AF management. Antiarrhythmic choice issue is discussed, with emphasis on individual approaches in choosing treat ment tactics.